PROSES SELEKSI PEGAWAI TIDAK TETAP DI SMA NEGERI 1 BOTUMOITO KABUPATEN BOALEMO - Sukrianto; Fibriyanti S Lakoro (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
SMA Country 1 Botumoito is an educational organization that requires additional human resources in carrying out the activities to be achieved. The purpose of the study was to determine the form of implementation of the non-permanent employee selection process in supporting the tasks and functions in SMA Country 1 Botumoito. The research method is descriptive qualitative. The informants in this study were the Head of SMA Country 1 Botumoito, the Head of Administration and Non-Permanent Employees. The data analysis technique used is the Spradley analysis model. The results of the study are as follows a) The system used in the selection of non-permanent employees at SMA Negeri 1 Botumoito must be carried out by carrying out the selection process of needs analysis, determining job descriptions, job specifications, socialization of acceptance, registration of admissions, selection and placement of non-permanent employees. b) File selection, has been carried out by looking at the administrative conditions of a person's requirements. Psychological and health tests to determine physical ability in carrying out the assigned tasks and interview tests were conducted to determine the ability of reasoning and thinking to analyze existing problems. c) Implementation of the selection process needs to have obstacles when producing non-permanent employees that support the implementation of work, especially in the administrative field of SMA Country 1 Botumoito, namely the incompatibility of competencies and educational qualifications of non-permanent employees with the right positions. The socialization of acceptance has not been carried out, it must be open through the mass media, where the simplicity of the selection has not been carried out by opening the running and orientation process before the placement of non-permanent employees at SMA Country 1 Botumoito.